The effect of new technologies on civic participation models - Holubiak, Nataliia (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
The development of new technologies will enable decentralization and freedom of communication for large numbers of people, by overcoming the barriers that once rendered direct participation of society unfeasible. The continued development of information and communication technologies (ICT) makes it possible for people to participate in political life. Today, the use of e-tools is becoming a way of adapting democracy to the needs of contemporary states and strengthening civil society. The aim of this paper is to answer questions about the essence of ICT and forms of civic engagement through electronic forms of participation. The author seeks answers to the following questions: How does ICT influence political processes? How do electronic communication systems create the conditions for the political engagement of citizens? Can the use of information technologies have a real impact on participation?

Rozwój nowych technologii umożliwia zdecentralizowanie i swobodę w komunikowaniu się wielkich mas ludzi, przyczynia się do nierealnego wcześniej przezwyciężania barier. Postępujący rozwój technologii informacyjnych powoduje, iż człowiek może stać się uczestnikiem życia politycznego. W dzisiejszym świecie wykorzystanie e-narzędzi staje się sposobem dostosowania demokracji do potrzeb współczesnych państw oraz wzmocnienia społeczeństwa obywatelskiego. Celem niniejszego tekstu jest odpowiedź na pytania o istotę technologii informacyjnych oraz o formy zaangażowania obywatelskiego za pośrednictwem elektronicznych form partycypacji. Autorka szuka odpowiedzi na pytania: Jak ICT wpływają na procesy polityczne? W jaki sposób systemy komunikacji elektronicznej tworzą warunki do politycznego zaangażowania obywateli? Czy zastosowanie technologii informacyjnych może mieć realny wpływ na formy partycypacji?
Wpływ nowych technologii na modele partycypacji obywatelskiej
Keywords: e-participation; information and communication technologies; electronic democracy; e-tools; e-partycypacja; technologie informacyjne; demokracja elektroniczna; e-narzędzia